Local Dynamics of the Hutchinson Equation with Two Delays in a Critical Case of a Resonance 1:2 - E. O. Kiseleva (Моделирование и анализ информационных систем)
A differential-difference equation arising at the description of dynamics of a population is considered. It is supposed that the parameters are chosen so that characteristic quasipolinom has two pairs of imaginary roots which are in resonance 1:2. The normal form of the equation, when the parameters are close to the critical values, is constructed. Phase reorganizations of a normal form under changes of parameters are studied.